KHALIFATULLAH PANATAGAMA : CONTINUITY & CHANGE IN THE PRACTICE OF POLITICAL ISLAM IN MODERN INDONESIA - Hari Zamharir; Mohammad Noer; Sahruddin Lubis (Universitas Nasional, 2020)
As the culminating point of long history of penetracion de pacifique of Islam across the archipelago of Indonesia (Nusantara), several Kingdoms of Islam emerged in the early 19th century of modern Indonesia. The kings not only perform the functions in political domain but also in religious matters; with the rulers being the guidance of Islamic law (syari’ah). Gaining the independence of the country in Mid 20th century ( 1945), this historical legacy continues to be tackled by the post-monarchy state of Republic Indonesia under the Ministry of Religious Affairs—but its legal basis was a controversy when the Indonesian Constitution,UUD 1945, was agreed upon, without explicit mention of the duties to be performed by Muslims to implement the Islamic law. Now that power politics in 2019 poses heated debate over the khilafah ideology and political system vis-a-vis Pancasila, it is interesting to look into deeper insights of the legacy of Khalitullah Panatagama. From the duality of nomocracy and democracy, the legacy could be re-interpreted to gain proper understanding of religion—politics relationship. The conceptual basis of the study is Habermasian’s claim of post-secular social science with its notion of the old-fashioned axioms of secularism under which modern politics has been in practice.